Analysis Of Factors Influencing The Decision Of Couples Of Childbearing Age (PUS) In Choosing Contraception In West Denpasar District - Wulan Atika Sari; Ida Ayu Nyoman Saskara; Made Kembar Sri Budhi; Ni Putu Martini Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Contraceptive methods are effective methods for delaying and spacing pregnancies and stopping fertility. Decision making in choosing a contraceptive device needs to consider the fertility needs and health conditions of the prospective contraceptive user. This research aims to: 1) To analyze the simultaneous influence of education level, income, husband's support, and the role of family planning officers on the decisions of couples of childbearing age (CCA) in choosing contraception in West Denpasar District. 2) To analyze the partial influence of education level, income, husband's support, and the role of family planning officers on the decisions of couples of childbearing age (CCA) in choosing contraception in West Denpasar District. This data uses primary data with a quantitative approach obtained from interviews and a combination of secondary data. The population of this study was 18,236 thousand people using 100 samples from this population. Data analysis techniques use descriptive statistical analysis, binary logistic analysis, model fit test, multiple linear analysis. These results show that: 1) education, income, husband's support, and the role of family planning officers simultaneously influence the decision to choose contraception in West Denpasar District. 2) education partially has a positive effect on the decision to choose contraception in West Denpasar District. 3) income partially has a positive effect on the decision to choose contraception in West Denpasar District. 4) husband's support partially has a positive effect on the decision to choose contraception in West Denpasar District. 5) the role of family planning officers partially has a positive influence on the decision to choose contraception in West Denpasar District.